The Influence of Product Quality, Promotion, and Brand Image on Customer Satisfaction Through Purchasing Decisions at Zam-Zam Stalls in Jakarta City - Hastari, Hilda; Basudani, Wahid Akbar (EAJ (Economic and Accounting Journal), 2026)
This study aims to analyze the effect of product quality, promotion, and brand image on customer satisfaction through purchasing decisions at zam-zam stalls. The development of the creative industry and event organizers has encouraged many restaurants now not only designed for dining comfort, but also carry the concept of attractive themes and decorations that make it an option for various events. Data was collected through questionnaires distributed to 95 respondents and using Structural Equation Modeling (SEM) with version 4.1.1.4 The results of this study indicate that product quality has a significant effect on purchasing decisions and customer satisfaction. Promotion has no significant effect on purchasing decisions but has a significant effect on customer satisfaction. Brand image has a positive effect on purchasing decisions and customer satisfaction. Purchasing decisions have a significant effect on customer satisfaction. Product quality and promotion have no direct influence on customer satisfaction through purchasing decisions. And brand image has a significant indirect effect on customer satisfaction through purchasing decisions. The findings of this study indicate that brand image is a factor that has an influence on customer satisfaction and purchasing decisions at zam-zam stalls.